Eruption fractal model applied to log-logistic volcanoes: Colima, Soufriere and Erebus - Brenes-André, José (2016)
The fractal model proposed in Brenes (2013), Brenes & Alvarado (2013), Brenes (2014) y Brenes (2016) is now expanded to include the empirical log-logistical relationship proposed in Connor et al. (2003) for Soufriere volcano, providing it with a theoretical basis. Such a theoretical derivation suggests a thermo-dynamical view of the eruption process.